Aluminium recycling activity on construction site: Malaysia case study - Rakiman, Umol Syamsyul; Raja Mohd Rasi, Raja Zuraidah; Ahmad Latiffic, Aryani (American Scientific Publishers, 2017)
Aluminium is largely used in transportation industry to make vehicles, but not all country has their own transportation industry. But nearly all country has their construction industry. With the rise of aluminium usage in the effort to save the environment, it is wise to identify the recycling activity on a construction site. This paper is about the identification of aluminium recycling activity on a construction site. Construction site is second to transportation in term of aluminium usage. A case study is conducted to identify the aluminium recycling activity on the construction site.This study is explorative in nature as different country has different conduct of recycling on site. Fromconducted case study, one main recycling activity is in the light which is collecting. Even though it is only one activity, it appears in many stages of the aluminium recycling activity. By having this knowledge, it might help the responsible party to set up standardised recycling procedure on the construction site while at the same time encourage the recycling activity.